(untitled) (Voice of Teacher, 2021)
The paper documents a Total 18 medicinal tree species belonging to 15 families within Padma Kanya Multiple Campus at Kathmandu district. The plants were surveyed through the direct visit of the field in different interval of time and identified their therapeutic values by using the help of secondary data such as available literatures and research papers. The plant parts most commonly used in medicine are roots, leaves, flowers, fruits, seeds, bark and whole plant. These plants are commonly used to cure diseases like cough, bronchitis, asthma, digestive problems and rheumatism etc. This study will be helpful to the students of this campus as a basic information for their research and practical works.